Fescue Hay Cost-Return Budget in Central and Eastern Kansas - Fogleman, Sarah L.; Warmann, Gerald W. (My University, 1999)
This publication provides estimated cost and returns for forward farm planning for fescue hay in central and eastern Kansas.
MF2146_1999_10
Keywords: MF2146; Crops; Economics; MF